This preview shows page 1. Sign up to view the full content.
Unformatted text preview: G for all t E t = C t + I t + G t Y t = E t which on straight substitution gives rise to the second-order nonhomogeneous recursive equation Y t − ( b + v ) Y t − 1 + vY t − 2 = a + G The particular solution is found by letting Y t = Y ∗ for all t . Hence Y ∗ − ( b + v ) Y ∗ + vY ∗ = a + G i.e. Y ∗ = a + G 1 − b In other words, in equilibrium, income equals the simple multiplier result. The complementary result, Y c , is obtained by solving the homogeneous compo-nent Y t − ( b + v ) Y t − 1 + vY t − 2 = which has the characteristic equation x 2 − ( b + v ) x + v = with solutions r , s = ( b + v ) ± ± ( b + v ) 2 − 4 v 2 11 Samuelson originally related investment to lagged consumption rather than lagged income....
View Full Document
This note was uploaded on 12/14/2011 for the course ECO 3023 taught by Professor Dr.gwartney during the Fall '11 term at FSU.
- Fall '11